Determinants of working capital management before, during, and after the global financial crisis of 2008: Evidence from Malaysia - Haron, Razali; Naji Mansour , Nomran (Western Illinois University, 2016)
Financial crisis that hit the economic standing in 2008 has put the blame on the mismanagement of the working capital of firms. Empirical evidences highlight the importance of efficient and sound working capital management thus managers should therefore be alert and sensitive on the factors affecting working capital management to improve firm’s performance in order to stay resilient. Nevertheless, limited studies have been done on this matter and is very much pronounced in the East Asian countries, despites the fact that these countries are the worst affected by the crisis. Malaysia is no exception in suffering from the turmoil thus it is paramount to examine the influencing factors of working capital management especially before, during and after a financial crisis in Malaysia. A panel regression is employed on a financial data of 57 Malaysian listed firms from 2002-2012. The study period is divided into three different scenarios, 2002-2006 (before the crisis), 2007-2008 (during the crisis) and 2009-2012 (after crisis). The cash conversion cycle is employed as a measurement of working capital management. The independent variables and their measurements are chosen based on previous studies, which are, profitability (net profit/total asset), debt (total debt/total asset), sales growth (salest–salest-1)/salest-1), free Cash flow (free cash flow/total asset), firm size (natural logarithm of sales) and liquidity (current asset/current liabilities). Several tests are carried out and the statistical procedure showed that the Random Effect model is the best model to explain the relationship between working capital management and its explanatory variables. A constant negative relationship is spotted between profitability and firm size with working capital management for all the three periods. The negative relationship between profitability and firm size with working capital management provide strong evidence on pecking order theory. Sales growth is negatively related to working capital management before and after the crisis periods. Debt appears to be mixed, with positive sign before the crisis but negative after the crisis. Free cash flow is positively related during the crisis period. No significant relationship however is detected on liquidity. The same variables (profitability, debt, sales growth and firm size) have significant relationships with working capital management before and after the crisis. This study has policy implication where managers can be sensitive on factors affecting working capital management and give particular attention on profitability, debt, sales growth and firm size in the management of their working capital regardless of the economic scenarios.